Specifying voting protocol using CSP - Ban, Ainita; Shukur, Zarina (2012)
Electronic voting can be seen as one of the best alternatives of today’s election for it will provide many advantages such as efficient and accurate data management and accumulation as well as convenience to voters. This paper presents work of specifying voting protocol formally using CSP (Communicating Sequential Process). The specification will be used in verifying properties of voting protocol.